KUALITAS PRODUK DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA UMKM DI JAKARTA - Aspizain Caniago; Agung Edi Rustanto (Journal of Management Small and Medium Enterprises (SMEs), 2022)
This study aims to determine the effect of Product Quality on Consumer Buying Interest. This research used a quantitative approach, with data collection techniques using a questionnaire. In this study, the research tests of validity, reliability, correlation analysis, descriptive analysis, simple linear regression, t-test and coefficient of determination were applied. The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothesis test results. The results of this study indicate that the Product Quality has a significant effect on Buying Interest. The contribution of the independent variable (Product Quality) to the dependent variable (Buying Interest) is 72.6%. Keywords: Product Quality, Consumer Buying Interest, Tokopedia